immuneACCESS
DOI: 10.21417/b7q639
|View full text |Cite
|
Sign up to set email alerts
|

High throughput T cell receptor sequencing identifies clonally expanded CD8+ T cell populations in Alopecia Areata

Abstract: AMC and RC are co-inventors on US Patent no. 9,198,911 filed by Columbia University and licensed to Aclaris Therapeutics. RC is a consultant for and shareholder of Aclaris Therapeutics. AMC is a consultant for Aclaris Therapeutics and Dermira and is a shareholder of Aclaris Therapeutics. AMC has received grant support from Pfizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…In concert with upregulation of both MHC class I and MHC class II molecules, our data suggest AA CD4 + and CD8 + T cells are clonotypically expanded, with extensive overlap of TCR sequences between different single-cell clusters (Figure 4). Notably, in the murine AA T cells, clonotypic overlap was seen predominantly in the C1 CD8 + CCR7 + , C2 IFN-γ-expressing, and C6 CD8 + CD103 + CTL clusters, in line with previous reports (33). The clonally expanded C6 cluster had the highest level of NKG2D (Klrk1) and demonstrated elevated JAK2/STAT5 and cytolytic gene sets ( Figure 3), paralleling evidence in prior murine and human AA of these putatively pathogenic pathways (4,5).…”
Section: Discussionsupporting
confidence: 86%
“…In concert with upregulation of both MHC class I and MHC class II molecules, our data suggest AA CD4 + and CD8 + T cells are clonotypically expanded, with extensive overlap of TCR sequences between different single-cell clusters (Figure 4). Notably, in the murine AA T cells, clonotypic overlap was seen predominantly in the C1 CD8 + CCR7 + , C2 IFN-γ-expressing, and C6 CD8 + CD103 + CTL clusters, in line with previous reports (33). The clonally expanded C6 cluster had the highest level of NKG2D (Klrk1) and demonstrated elevated JAK2/STAT5 and cytolytic gene sets ( Figure 3), paralleling evidence in prior murine and human AA of these putatively pathogenic pathways (4,5).…”
Section: Discussionsupporting
confidence: 86%
“…The development of alopecia areata is associated with the collapse of HF immune privilege which subsequently increases antigen presentation to surveying T cells that recognize HF epithelial and/or melanocyteassociated antigens as foreign, and mount autoimmune responses against HFs [93,[97][98][99][100]. There are ongoing investigations trying to identify the exact HF antigen and antigen-specific T cells involved in the onset of alopecia areata [99,101]. The autoimmune attack does not kill HFSCs specifically, but, instead, the lower transient portion of anagen HFs [97].…”
Section: Influx Of Auto-reacting T-cells Into Hfsc Niche Disrupts Haimentioning
confidence: 99%
“…Thus the important ongoing search for elusive autoantigens and specific autoreactive CD8 1 T cells in AA research [49][50][51] might well turn out to be less crucial in terms of effective therapeutic intervention in patients with AA than the protection and restoration of HF IP. 3 Instead, a more sustained therapeutic research focus on upregulating or administering HF IP ''guardians,'' such as a-MSH, calcitonin gene-related peptide, and VIP, 14,48 and on counteracting the potently IP collapsepromoting neuropeptide substance P 52,53 might generate more universally effective treatment and have a more direct benefit in future AA management.…”
Section: Do Autoantigen Responses Play a Primary Or Secondary Role Inmentioning
confidence: 99%
“…26 This was rapidly confirmed independently at the genomic level in a major genome-wide association study. 51 The subsequent finding that transfer of autologous CD56 1 NKG2D 1 cells suffices to transform a completely normal human HF into one that shows all the key signs of human AA 45 not only provided the first functional evidence of a key role of NKG2D 1 cells in human AA pathobiology but also strongly suggested that specific HF autoantigens are not indispensable for the development of AA lesions (Fig 1, A), thus further supporting the notion that autoantigens could play a secondary role in human AA, at least in many affected patients. The large amounts of IFN-g produced by the transferred CD8/NKG2D cells 45,74 are thought to induce a ''cytokine storm'' effect in healthy human scalp skin xenotransplants, which breaks down HF IP and initiates the cascade of alopecia-promoting events depicted in Fig 4, A and B.…”
Section: Humanized Mouse Models Of Aa As a Unique Resource For Illumimentioning
confidence: 99%